Study of corrosion behaviour of Al2O3-13 % TiO2 and Cr2O3 coated ship hull steel in 3.5% NaCl solution. Issue 1 (July 2021) - Sharma, Aaishwarika Raj; Goyal, Rakesh
Abstract: Corrosion degradation of ship hull plates is an important aspect responsible for failure of ships in marine environment. Surface coatings are being used to protect the metallic materials from corrosion. In this work, Al2 O3 -13 % TiO2 coating and Cr2 O3 coating were deposited on ship hull building material using D-gun flame spray method. The corrosion behaviour of coatings and substrate was investigated using cyclic polarization test. The microstructure and phase composition of coatings were analysed by scanning electron microscopy (SEM) and electron dispersive spectrum (EDS). The corrosion rate was evaluated from the corrosion parameters extracted from graphs. The uncoated and coated substrates were compared on the basis of corrosion parameters.